PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR - M. Riski Saputra; Eko Kuntarto; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The results of this study show that the role of the principal's leadership in improving teacher performance at the elementary school level, specifically regarding the principal’s leadership in enhancing teacher performance, involves three main stages: systematic organization, implementation, and evaluation. The principal acts as an educator, manager, administrator, supervisor, leader, creator of a conducive work climate, and entrepreneur. In the organizational stage, the principal develops teacher competency improvement programs through regular meetings, academic supervision, and professional development. The implementation of leadership is reflected in clear task delegation, supervision scheduling, and the management of school administration to support effective teaching and learning processes. Evaluation is carried out periodically through supervision, direct observation, and performance monitoring during regular meetings.As a leader, the principal formulates the school’s vision and mission and creates a positive work environment by improving facilities and fostering harmonious relationships among school members. Additionally, the principal takes on the role of an entrepreneur by developing entrepreneurship programs to enhance school resources. Supporting factors for the principal’s leadership include the support of teachers, staff, and parents, as well as the availability of facilities and training opportunities. On the other hand, the challenges faced include budget constraints, lack of human resources, and rapid policy changes. To overcome these obstacles, the principal adopts adaptive and collaborative leadership strategies. With effective leadership, teacher performance is expected to improve, thereby positively impacting the quality of education at the school. Based on the research findings, it can be concluded that in carrying out the role of leadership to improve teacher performance, the principal has made significant efforts to enhance the quality of education in the school. One such effort includes improving teacher performance and professionalism.